Progressive and Error-Resilient Transmission Strategies for VLC Encoded Signals over Noisy Channels - Guillemot Christine; Jégou Hervé (EURASIP Journal on Advances in Signal Processing, 2006)
This paper addresses the issue of robust and progressive transmission of signals (e.g., images, video) encoded with variable length codes (VLCs) over error-prone channels. This paper first describes bitstream construction methods offering good properties in terms of error resilience and progressivity. In contrast with related algorithms described in the literature, all proposed methods have a linear complexity as the sequence length increases. The applicability of soft-input soft-output (SISO) and turbo decoding principles to resulting bitstream structures is investigated. In addition to error resilience, the amenability of the bitstream construction methods to progressive decoding is considered. The problem of code design for achieving good performance in terms of error resilience and progressive decoding with these transmission strategies is then addressed. The VLC code has to be such that the symbol energy is mainly concentrated on the first bits of the symbol representation (i.e., on the first transitions of the corresponding codetree). Simulation results reveal high performance in terms of symbol error rate (SER) and mean-square reconstruction error (MSE). These error-resilience and progressivity properties are obtained without any penalty in compression efficiency. Codes with such properties are of strong interest for the binarization of -ary sources in state-of-the-art image, and video coding systems making use of, for example, the EBCOT or CABAC algorithms. A prior statistical analysis of the signal allows the construction of the appropriate binarization code.